Structure-Function Analysis of Immunity Proteins of Pediocin-Like Bacteriocins: C-Terminal Parts of Immunity Proteins Are Involved in Specific Recognition of Cognate Bacteriocins - Johnsen, Line (American Society for Microbiology, 2004)
The immunity proteins of pediocin-like bacteriocins show a high degree of specificity with respect to the pediocin-like bacteriocin they recognize and confer immunity to. The aim of this study was to identify regions of the immunity proteins that are involved in this specific recognition. Six different hybrid immunity proteins were constructed from three different pediocin-like bacteriocin immunity proteins that have similar sequences but confer resistance to different bacteriocins. These hybrid immunity proteins were then tested for their ability to confer immunity to various pediocin-like bacteriocins. The specificities of the hybrid immunity proteins proved to be similar to those of the immunity proteins from which the C-terminal halves were derived, thus revealing that the C-terminal half of immunity proteins for pediocin-like bacteriocins contains a domain that is involved in specific recognition of the bacteriocins they confer immunity to. Moreover, the results also revealed that the effectiveness of an immunity protein is strain dependent and that its functionality thus depends in part on interplay with strain-dependent factors. To further investigate the structure-function relationship of these immunity proteins, the enterocin A and leucocin A immunity proteins (EntA-im and LeuA-im) were purified to homogeneity and structurally analyzed under various conditions by Circular dichroism (CD) spectroscopy. The results revealed that both immunity proteins are α-helical and well structured in an aqueous environment, the denaturing temperature being 78.5°C for EntA-im and 58.0°C for LeuA-im. The CD spectra also revealed that there was no further increase in the structuring or α-helical content when the immunity proteins were exposed to dodecylphosphocholine micelles or dioleoyl-l-α-phosphatidyl-dl-glycerol (DOPG) liposomes, indicating that the immunity proteins, in contrast to the bacteriocins, do not interact extensively with membranes. They may nevertheless be loosely associated with the membrane, possibly as peripheral membrane proteins, thus enabling them to interact with their cognate bacteriocin.